Health research methodology education in Canadian emergency medicine residency programs: A national environmental scan - Wang, Aaron; Meiwald, Allison; Harper, Robert; Van Aarsen, Kristine; Yan, Justin (Canadian Medical Education Journal, 2020)
Objectives: Our objective was to describe the variability of research methodology teaching among English-speaking Royal College of Physicians and Surgeons of Canada emergency medicine (RCPSC-EM) residency programs. We also aimed to identify barriers to teaching research methodology curricula. Methods: An electronic survey was sent by email to program directors and residents of English-speaking RCPSC-EM training programs countrywide. Reminder emails were sent after 2, 4, and 8 weeks. Quantitative, descriptive statistics were prepared, and qualitative data and themes were identified. Results: We received a total of 7 responses from the possible 12 program directors (response rate = 58.3%). Out of 354 potential resident respondents, 82 (23.2%) completed the survey. There was disparity between resident and program director responses with respect to the existence of curricula, preparation for Royal College exams, and usefulness for future practice. Barriers to teaching a research methodologies curriculum included lack of time, support, educated faculty, and finances. Conclusion: This survey demonstrates that Canadian EM residency programs vary with respect to research methodology curriculum, and discrepancies exist between residents’ and program directors’ perceptions of the curriculum. Given the lack of a standardized research methodology curriculum for these programs, there is an opportunity to improve training in research methodology.